Marine Heat as a Renewable Energy Source - Wayan Suparta (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2020)
The ocean, which covers two-thirds of the land surface, receives heat from the sun's rays. Ocean water also receives heat that comes from geothermal heat, which is magma located under the seafloor. Ocean surface temperatures are warmest near the equator, with temperatures from 25°C to 33°C between 0 degrees and 20 degrees north and south latitude. This temperature difference can be utilized to run the driving machine based on the thermodynamic principle. A technology called Ocean Thermal Energy Conversion (OTEC) is capable of converting the temperature difference into electrical energy. OTEC is a power plant by utilizing the difference in the temperature of seawater on the surface and the temperature of deep seawater. This paper briefly overviews of how ocean heat can be utilized as a renewable energy source to produce electrical energy. The development and exploitation of renewable marine energy in the future are feasible and this will involve multidisciplinary fields such as robotics and informatics.